Comparative study on bladder tapping and cold saline application in initiation of micturition among 1-3 years children. - Acharya,Rachana (2017)
ABSTRACT: Background Urine collection in children, especially toddlers is really a challenging yet vital job in our setting where UTI is common cause of febrile illness in this age group. For urine collection, a wide range of clinical interventions including non-invasive and invasive methods is described. Clean catch urine collection is recommended by WHO and NICE guidelines as well. Researches are being done in the entire globe on collecting clean urine sample by triggering early childhood cutaneous voiding reflexes; one is bladder tapping another is suprapubic cold saline application. Both of these techniques are non-invasive and quick with good success rate yet we want to compare these two techniques to find out the efficacies. Primary Objective: To compare the efficacy of two voiding stimulation methods-bladder tapping and suprapubic cold saline application for the initiation of micturition. Secondary Objective: To find the association of success rate of initiation of micturition among the selected demographic variables of children. Methods A comparative interventional research was conducted at Pediatric Department of BPKIHS, Nepal, including 60 children of age 1-3 years. The first sample was taken by lottery method, then consecutively children were recruited in each group until the 30 children in each group was obtained. Twenty five minutes after feeding, the standard set of steps for two intervention methods were followed. Success was defined as micturition even a drop of urine sample within 5 min of staring the stimulation maneuver. Results With 60 children aged 1-3 years, (mean age of 20.67 ±7.18 months) 30 children in each intervention group and male-female ratio 3:2, overall success rate in initiating micturition was 65% (39/60). It was 70% (21/30) in Bladder Tapping (BT) group and 60% (18/30) in Cold Saline Application (CSA) group. The overall mean time for initiation of micturition was 135.97±72.07sec (2.26min), and it was more or less similar in both groups. There was no significant difference in rate of success according to age and gender. It was significant in less than 10 kg of children where there was higher success rate of voiding in Bladder Tapping (BT) group. Conclusion The study suggests that Bladder Tapping and Cold Saline Application (Quick-Wee Method) both are quick safe and effective way of collecting CCU, with Bladder Tapping more effective among less than 10 kg children. Key Words Bladder Tapping, Cold Saline Application, Quick-Wee Method, Clean Catch Urine, Toddlers, Urinary Tract Infection